EFFECTS OF TWO PLANT EXTRACTS AND VITAMIN D3 ON BONE MECHANICAL AND HISTOLOGICAL PROPERTIES OF BROILER CHICKENS - M. T. Mirakzehi; S. J. Hosseini; H. Saleh (Journal of Animal and Plant Sciences, 2018)
This study was performed to evaluate the effects of hydroalcoholic extracts of Withania somnifera (WS) root, Withania coagulans (WC) fruit and 1, 25-dihydroxycholecalciferol [1, 25-( OH) D ] on bone mineralization, mechanical ,and 2 3 histological properties of broiler chickens. A total of 550 male one-day-old Ross 308 broiler chickens were randomly allotted to 55 pens, with 10 birds per pen ( replicate) , and reared for 42 days. A completely randomized design was used with 11 dietary treatments including a positive control diet with adequate Ca; a negative control diet (Ca concentration reduced by 30%); and a negative control diet supplemented with either WS or WC extracts at three levels (0, 75 and 150 mg/kg diet) or 1, 25-( OH) -D at two different levels (0 and 0.5 ¼g/kg diet). Diets were givenad libitum from one to 42 2 3 day of age. Dietary treatments did not affect feed intake and feed conversion efficiency. On days 21 and 42, one bird per replicate was killed and tibiae were removed. Among the birds that were given negative control diet, the highest Ca retention values were noted in those that received 75 mg/kg WC (84.67%) or 150 mg/kg WS ( 83.09%) with 0.5 ¼g/kg1, 25-(OH) D . At 21 days of age, the highest tibia Ca values were obtained in birds fed negative control diet 2 3 supplemented with 150 mg/kg WS or WC with no dietary supplementation of 1, 25-(OH) D (38.652 and 38.433 % 2 3 respectively). No significant effects on tibia Ca were noted at 42 days. There were no significant differences (P>0.05) between experimental treatments for all tibia bone biomechanical properties. The addition of 75 mg/kg WS and 1, 25- (OH) D to negative control diets resulted in significant increase (P<0.05) in tibia mineralized zone width. The present 2 3 study showed that dietary supplementation of WS and WC at 150 and 75 mg/kg, respectively improved Ca retention and the effects were more pronounced in the presence of 1, 25 ( OH) D . Administration of 150 mg/kg WS and WC had 2 3 beneficial effects on bone calcification. Also, synergistic effects of WS and 1, 25-(OH) D resulted in significant 2 3 increase in tibia mineralized zone width. the development of bone mineralized zone was reported
Keywords: Withania somnifera; Withania coagulans; 1; 25-dihydroxycholecalciferol; Bone; Broiler chicken.